Effect of an innovative training program on the clinical performance of Physical Therapy interns - Grageda, Maria Elizabeth M. (2002)
his research describes the entry-level clinical competencies of Physical therapy interns and how it compares with the expected entry-levels set by their clinical supervisors. This study also aims to look at the significance of academic affiliation to the student's entry-level skills, knowledge, and attitude. Lastly, this study also aims to look at the effect of an innovative training program in helping the interns achieve the expected exit competencies. A pre-experimental study design with a one-group pretest posttest design was used in the implementation of the study. Forty-three PT interns from the University of the Philippines and the University of the East Ramon Magsaysay Memorial Medical Foundation, underwent training at the Philippine General Hospital Physical Therapy Section from August 2001 to January 2002. The implementation of study was divided into four major phases: gathering information, re-designing of the training program based on the information gathered, actual implementation of the program and lastly, evaluation. Results of the study show that the actual entry-level knowledge and attitude of the students are higher than what is expected from them by the clinical supervisors, but the students are higher than what is expected from them by the clinical supervisors, but the entry-level skills are lower than the expected level, more so in communication and patient management. No significant difference between the entry-level scores of the students based on their academic affiliation was noted. Based on results of the post-tests, it was seen that the exit level was met, with a more significant increase improvement in the intern's clinical skills and attitude, than in their clinical knowledge. Comparing the pre-test and the post-test results, it was seen that there was a significant increase in the skills, knowledge and attitude of the interns, again with a much higher improvement in their clinical skills, than clinical knowledge in patient assessment, communication, and patient management. The results show the importance of designing training programs based on objective information regarding the actual entry-level knowledge, skills and attitude of students, and not merely on the clinical instructor's expectations and assumptions. Knowing the actual entry-level competencies of the students will help in re-designing the program to make it more relevant to the students. Training programs were meant to adapt to the needs of the particular students currently undergoing training. What worked for one batch may not work for another. The results of this study also show that training programs should be made dynamic and innovative so that it will become relevant to the needs of the students. Each individual student and each batch of students will have different capabilities and this should be greatly considered in the design of the program. A strict program that does not adapt to the needs of the students does not maximize not only the learning opportunities, but also the potentials of the individual student. Efforts from clinical training program developers and implementers should be made to objectively determine the entry-level capacities of the students prior to start of training. Administration of a diagnostic tool, and analyzing and actually using the results in the re-designing of the program will greatly help in making the program relevant to the students' needs. All sources of information should also be considered: results of diagnostic examinations, self-assessment of the students, clinical supervisors and educators, academic instructors and past experiences of both the interns and the clinical supervisors. Based on the results of this study, the author recommends that educators involved in the development and implementation of clinical training programs apply the principles of data gathering and diagnostic testing prior to actual training to make the program more relevant to the needs of the student. Adequate time should also be given to analyze the results of these diagnostic tools, so that the results may be considered in the re-design of the training program. The four phases identified may be utilized by clinical program designers to suit the needs of their particular institution and students.
Published in MCU Res Journal 2011 v2, p29-35
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Physical therapy -- Study and teaching (Residency)